Techno-economic analysis of commercial size grid-connected rooftop solar PV systems in Malaysia under the NEM 3.0 scheme - Husain, Alaa A. F.; Ahmad Phesal, Maryam Huda; Ab Kadir, Mohd Zainal Abidin; Ungku Amirulddin, Ungku Anisa (MDPI AG, 2021)
Commercial grid-connected rooftop solar PV systems are widely applied worldwide as part of affordable and clean energy initiatives and viable long-term solutions for energy security. This is particularly true in a crowded city where space is a constraint and at the same time, there are unutilized rooftops. With the recently announced Net Energy Metering (NEM) 3.0, commercial buildings in Malaysia can apply up to 75% capacity of the maximum demand (MD), which can be connected to the grid. Apart from reducing electricity bills, the owner can offset energy for 10 years. This paper presents a design analysis with the details of the sizing of a rooftop PV system. The PVsyst software tool is used to estimate the energy produced by a 380 kWp system, and this study provides a financial analysis to evaluate the profitability of the system with a particular interest in commercial buildings under the NEM 3.0 policy, which has resulted in 8.4 years return of investment (ROI). PVsyst is a software used to size the PV system and provides technical, financial, and environmental analysis. This in-depth analysis could provide a useful case study for asset owners in deciding the way forward for sustainable energy production, cost saving, and combating the energy security issue, since Malaysia is blessed with an abundance of sunshine throughout the year.